Pengaruh Kegiatan Ice Breaking Wire Game Terhadap Konsentrasi Belajar Anak Usia Dini: Quasi Eksperimen di TK Al-Barokah - Aini, Nur; Nugraha, Dadan; Hendri Mulyana, Edi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study aims to determine the effect of ice breaking wire game activities on the concentration of early childhood learning. This study is based on the low level of children's concentration in the learning process which causes them to be easily distracted and have difficulty in completing tasks. The method used is a quasi-experiment with a sample of 8 people in group B at Al-Bayyinah Kindergarten as the control class and 8 people in group B at Al-Barokah Kindergarten as the experimental class. The data collection technique uses an observation sheet that covers three aspects of concentration, namely focus, duration of attention and suitability in working. The analysis used is descriptive statistics to describe data in both numerical and visual forms while inferential statistics to draw conclusions about a population based on data. The results of the study showed that there was a significant increase in children's learning concentration in the experimental class after being given treatment in the form of ice breaking wire game activities. This is evidenced by the N-gain value of the experimental class of 0.88 with a high category, while the N-gain value of the control class was only 0.093. In addition, it can be seen from the Mann Whitney U test the Asymp value. Sig.(2-tailed) 0.002 which is less than 0.05. Therefore, it can be concluded that Ha is accepted and Ho is rejected which means that there is an influence of the effectiveness of ice breaking wire game activities in developing the learning concentration abilities of early childhood children and there is a difference in the learning concentration abilities of early childhood children from both the experimental and control classes